A Simplified Quadrature Approach for Computing Bermudan Option Prices. (17th June 2016) - Simonato, Jean‐Guy
Abstract: We examine a simple quadrature approach to compute the prices of Bermudan options when the value of the corresponding European claim can be computed in closed form, one period before maturity. Using a constant grid of stock prices at early exercise time points, the known value of the European option is used as a smoothing device to enable efficient numerical integ ration with quadrature approaches. Examples with the geometric Brownian motion context and the lognormal jump‐diffusion context are provided.